Administrative Accountability of Officials for The Receipt of Goods Not In Accordance with The Contract - Andi Yuliadi; Sami'an Sami'an; Sarwono Hardjomuljadi (International Journal Labs, 2025)
The receipt of goods that are not in accordance with the contract in government procurement is one of the main sources of state losses, contractual disputes, and legal uncertainty in the implementation of projects. Receiving officials, such as Commitment Making Officials (PPK), Work Results Recipients (PPHP), and technical teams, have inherent legal and administrative responsibilities in ensuring the suitability of specifications, quality, quantity, and delivery time of goods. This article discusses the form of administrative accountability when officials receive goods that are not in accordance with the contract, reviewed from the legal framework of government procurement, the principle of legal certainty, the principle of accountability, and the legal norms of state administration. Through a juridical-normative approach, this study examines the relationship between official authority, standard operating procedures (SOPs), the risk of administrative irregularities, and legal consequences such as administrative sanctions, compensation demands, and potential unlawful acts by the ruler (onrechtmatige overheidsdaad). The findings show that the receipt of goods not in accordance with the contract not only violates the provisions of the PBJ Presidential Regulation, but is also a failure to implement the principle of legal certainty and the principle of prudence, which can result in administrative accountability and even ASN discipline. This article recommends strengthening the technical verification mechanism, digital governance in the inspection of goods, and reformulation of SOPs for receipt of goods to prevent contract deviations.